Intermolecular desymmetrizing gold-catalyzed Yne-Yne reaction of push-pull diarylalkynes - Claus, Vanessa; Wurm, Thomas; Vethacke, Vanessa; Dietl, Martin C.; Rudolph, Matthias; Rominger, Frank; Xie, Jin; Hashmi, A. Stephen K. (Chemistry - a European journal, 2018)
Push-pull diaryl alkynes are dimerized in the presence of a cationic gold catalyst. The polarized structure of the applied starting materials enables the generation of a highly reactive vinyl cation intermediate in an intermolecular reaction. Trapping of the vinyl cation by a nucleophilic attack of the electron-poor aryl unit then leads to the selective formation of highly substituted naphthalenes in a single step and in complete atom economy.